THE USE OF VLOGGING TO IMPROVE THE STUDENTS’ SPEAKING SKILL - Ayu Rahmawati; Bambang Harmanto; Niken Reti Indriastuti (EDUPEDIA, 2018)
The subject of this research was the students at the 11th grade IPA 3 of SMA Muhammadiyah 1 Ponorogo in the academic year 2016/2017, which consisted of 28 students. The research was started on April 04th 2017 until April 27th 2017. The research was conducted for two cycles and six meetings. The purpose of this research was to find out whether vlogging improve students’ speaking skill at the 11th grade of SMA Muhammadiyah 1 Ponorogo in the academic year of 2016/2017. This research was conducted by the researcher and the collaborator. The researcher took a part as a teacher who taught English and the collaborator took a part in this research as observer. The researcher used three instruments. The instruments were observation checklist, questionnaire, and test. The researcher observed the students’ activeness and interest using observation checklist, observed the students’ responses using questionnaire sheet, and measured the students’ speaking skill using test. The form of the test was oral test. The result of observation checklist showed that the classroom situation more conducive. The students were active and interested in the teaching and learning process. The result of questionnaire showed that the students became more interested, confident, and enjoy practice to speaking English by using vlogging. The result of the test showed the improvement from cycle I up to cycle II. The students’ score percentage in cycle I was 53.57%. Meanwhile, the students’ score percentage in cycle II was 100%. The researcher concluded that the implementation of vlogging to improve the students’ speaking skill at the 11th grade IPA 3 of SMA Muhammadiyah 1 Ponorogo in the academic year 2016/2017 was successful.